Human Mast Cell Line HMC1 Expresses Functional Mas-Related G-Protein Coupled Receptor 2 - Hermans, Maud A. W.; van Stigt, Astrid C.; van de Meerendonk, Sanne; Schrijver, Benjamin; van Daele, Paul L. A.; van Hagen, Petrus M.; van Splunter, Marloes; Dik, Willem A. (Frontiers in Immunology, 2021)
The Mas-related G-protein-coupled receptor X2 (MRGPRX2) is prominently expressed by mast cells and induces degranulation upon binding by different ligands. Its activation has been linked to various mast cell-related diseases, such as chronic spontaneous urticaria, atopic dermatitis and asthma. Therefore, inhibition of MRGPRX2 activity represents a therapeutic target for these conditions. However, the exact pathophysiology of this receptor is still unknown. In vitro research with mast cells is often hampered by the technical limitations of available cell lines. The human mast cell types LAD2 and HuMC (human mast cells cultured from CD34+ progenitor cells) most closely resemble mature human mast cells, yet have a very slow growth rate. A fast proliferating alternative is the human mast cell line HMC1, but they are considered unsuitable for degranulation assays due to their immature phenotype. Moreover, the expression and functionality of MRGPRX2 on HMC1 is controversial. Here, we describe the MRGPRX2 expression and functionality in HMC1 cells, and compare these with LAD2 and HuMC. We also propose a model to render HMC1 suitable for degranulation assays by pre-incubating them with latrunculin-B (Lat-B). Expression of MRGPRX2 by HMC1 was proven by RQ-PQR and flowcytometry, although at lower levels compared with LAD2 and HuMC. Pre-incubation of HMC1 cells with Lat-B significantly increased the overall degranulation capacity, without significantly changing their MRGPRX2 expression, phenotype or morphology. The MRGPRX2 specific compound 48/80 (C48/80) effectively induced degranulation of HMC1 as measured by CD63 membrane expression and β-hexosaminidase release, albeit in lower levels than for LAD2 or HuMC. HMC1, LAD2 and HuMC each had different degranulation kinetics upon stimulation with C48/80. Incubation with the MRGPRX2 specific inhibitor QWF inhibited C48/80-induced degranulation, confirming the functionality of MRGPRX2 on HMC1. In conclusion, HMC1 cells have lower levels of MRGPRX2 expression than LAD2 or HuMC, but are attractive for in vitro research because of their high growth rate and stable phenotype. HMC1 can be used to study MRGPRX2-mediated degranulation after pre-incubation with Lat-B, which provides the opportunity to explore MPRGRX2 biology in mast cells in a feasible way.